Ethiopian aging policy: A review of existing frameworks in relation to the Madrid International Plan of Action on Aging - Ahmed Muhye Seid; Netsanet Fentahun Babbel (Elsevier, 2023)
Background: The increasing life expectancy and the growing number of older people are becoming public health challenges, warranting the need for appropriate policy tools. Existing policy frameworks should prioritize and cover the public health demands of elders. However, there is a lack of concrete evidence on the existing policy tools and programs targeting elders in Ethiopia. Objective: This study was to explore the existing policies, programs, and interventions for elderly people in Ethiopia. Study design: A descriptive qualitative study using phenomenological approach and secondary data review wa conducted. Methods: A combination of systematic desk reviews of relevant policy and program documents and key informant interviews (KIIs) was used to capture data. Four purposefully selected interviews, based on their expertise, rich experience, in-depth understanding, and direct involvement in the policy environment, were conducted. Face-to-face interviews with the Audio recorder were employed during KII. The number of KIIs was limited to four, the point of theoretical saturation where no further new and informative themes were identified. Interview audios were transcribed, translated, and analyzed in thematic descriptive analysis. The United Nations Madrid International Plan of Action on Aging was used as a guideline for the data extraction process from relevant documents. Results: A total of 221 documents were retrieved, and 75 met the inclusion criteria. We identified four interconnected main themes and 11 sub-themes of concern for the elderly. Ethiopia recognized old people as vulnerable in various national legal and policy documents, including the constitution, population policy, and development plans. Surprisingly, no government policy exists in Ethiopia to address the health and nutritional problems of the elderly in particular. Conclusion: Though Ethiopia is facing demographic transition, no specific old-age policies, programs, or interventions are being implemented. Hence, the government and relevant stakeholders should strive to design and implement an old-age policy outlining cost-effective interventions for elders.